1994
DOI: 10.1002/jcb.240550208
|View full text |Cite
|
Sign up to set email alerts
|

Signal peptide hydrophobicity is finely tailored for function

Abstract: In order to titrate the dependence of individual steps in protein transport on signal peptide hydrophobicity, we have examined a series of mutants which involve replacement of the hydrophobic core segment of the Escherichia coli alkaline phosphatase signal peptide. The core regions vary in composition from 10:0 to 0:10 in the ratio of alanine to leucine residues. Thus, a nonfunctional polyalanine-containing signal peptide is titrated with the more hydrophobic residue, leucine. Analysis of this series identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
29
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 49 publications
4
29
0
Order By: Relevance
“…We find that for signal peptides of comparable size, the extent to which the signal peptide in the second position is utilized depends solely on its hydrophobicity relative to the first. Furthermore, the pattern observed here parallels the precursor accumulation of wildtype ␤-lactamase that we observe when it is coexpressed with alkaline phosphatase carrying signal peptides of various hydrophobicity levels (36). A model for the utilization of one signal peptide or the other is shown diagrammatically in Fig.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…We find that for signal peptides of comparable size, the extent to which the signal peptide in the second position is utilized depends solely on its hydrophobicity relative to the first. Furthermore, the pattern observed here parallels the precursor accumulation of wildtype ␤-lactamase that we observe when it is coexpressed with alkaline phosphatase carrying signal peptides of various hydrophobicity levels (36). A model for the utilization of one signal peptide or the other is shown diagrammatically in Fig.…”
Section: Discussionsupporting
confidence: 76%
“…2 and 3. The leucine-rich segments show mobility changes in sodium dodecyl sulfate-polyacrylamide gel electrophoresis (36) with the mobility of the high-molecular-weight species for WT-8L2A being consistent with the precursor species (p*). W, wholecell sample; P, periplasmic fraction.…”
Section: Figmentioning
confidence: 72%
See 2 more Smart Citations
“…However, MtlA inserted into membranes normally in the presence of reduced levels of SecA. Second, Rusch et al (18) have characterized the export of alkaline phosphatase precursors as a function of the relative hydrophobicity of their signal sequences. They found that signal sequences with very high hydrophobicity mediated precursor export that was not detectably inhibited by treatment of cells with NaN 3 .…”
Section: Discussionmentioning
confidence: 99%